INFLASI, KEMISKINAN DAN TINGKAT PENGANGGURAN DI INDONESIA (2013-2022) - Diki Alvique Wibowo (Journal of Development Economic and Social Studies, 2023)
Inflation and unemployment are thorny problems that are always faced by the State of Indonesia related to the lack of quality of economic growth. The Phillips curve which describes the tradeoff between inflation and unemployment does not apply in Indonesia. This type of research is quantitative with descriptive statistics used to analyze data by describing or describing the data that has been collected as it is without intending to make conclusions. The research results show that Indonesia's poverty rate and open unemployment rate for the 2013-2022 period are highest in 2013 while inflation, poverty rate and Indonesia's open unemployment rate for the 2013-2022 period are in 2021, but there is a difference in 2021 the open unemployment rate became the highest unemployment compared to the unemployment rate in the period 2013-2022.